1996
DOI: 10.1007/bf00011163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals on peppermint and cornmint

Abstract: Heavy metal pollution of agricultural soils and air is one of the most severe ecological problems on a world scale and in Bulgaria in particular. The biggest sources of pollution in Bulgaria are some non-ferrous metals smelters, such as the Non -Ferrous Metals Combine (NFMC) near Plovdiv, situated on very fertile soils. Vegetable, arable and animal production in this area results in contaminated produce with excessive amounts of Cd, Pb, Cu, Mn and Zn.In order to discover some crops which could be grown on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(85 citation statements)
references
References 17 publications
11
73
1
Order By: Relevance
“…With time, mint plants seemed to have adjusted to the cultivation conditions in the presence of biosolids, because they no longer showed differences in dry matter values when grown in the presence of different levels of solids residues. These results were in agreement with those of Zheljazkov and Nielsen (1996) and Scora and Chang (1997), because the mint plants were capable of developing without accumulation of these metals in their tissues. When mint plants were evaluated as for dry matter of stem plus petiole (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…With time, mint plants seemed to have adjusted to the cultivation conditions in the presence of biosolids, because they no longer showed differences in dry matter values when grown in the presence of different levels of solids residues. These results were in agreement with those of Zheljazkov and Nielsen (1996) and Scora and Chang (1997), because the mint plants were capable of developing without accumulation of these metals in their tissues. When mint plants were evaluated as for dry matter of stem plus petiole (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In all evaluation periods, a higher value for root dry matter was observed in the plants grown without biosolid. The increase in the residue levels was accompanied by a decrease in root dry matter, which suggested the phytoremediator action of mint plants (Zheljazkov and Nielsen, 1996;Scora and Chang, 1997). Maisonnave et al (2002) observed that the roots of grass plants grown on biosolids assimilated high levels of heavy metals obstructing their translocation to other plant parts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al (1993) observed increased synthesis of ginsenosides in Panax quinquefolium L. plants. On the other hand, field experiments with Mentha piperita L. and Mentha arvensis L. grown on strongly contaminated soil in the vicinity of a smelting plant for non-ferrous metals, showed a decreased yield of fresh herbage but the content of essential oil was not affected by contamination of soil with heavy metals (Zheljazkov and Nielsen 1996).…”
Section: The Content Of Secondary Metabolites In Chamomile Anthodiamentioning
confidence: 98%
“…Similar results were obtained for peppermint and cornmint, where no heavy metal contamination was found in the essential oils. Despite of the yield reduction (up to 14%) caused by heavy metal contamination, mint still remained a very profitable crop and it could be used as substitute for other crops (Zheljazkov and Nielsen 1996a). Other industrial crops suggested for cultivation on metal contaminated soils were fibre plants like flax, cotton, hemp (e.g., Yanchev et al 2000, Angelova et al 2004 and energy crops, such as Salix trees and reed canary grass (Börjesson 1999).…”
Section: Crop Rotation and Growing Of Industrial Cropsmentioning
confidence: 99%